Genetic predisposition in nonalcoholic fatty liver disease - Sookoian, Silvia Cristina (2017)
Nonalcoholic fatty liver disease (NAFLD) is the most common chronic liver disease whose prevalence has reached global epidemic proportions. Although the disease is relatively benign in the early stages, when severe clinical forms, including nonalcoholic steatohepatitis (NASH), cirrhosis and even hepatocellular carcinoma, occur, they result in worsening the long-term prognosis. A growing body of evidence indicates that NAFLD develops from a complex process in which many factors, including genetic susceptibility and environmental insults, are involved. In this review, we focused on the genetic component of NAFLD, with special emphasis on the role of genetics in the disease pathogenesis and natural history.Insights into the topic of the genetic susceptibility in lean individuals with NAFLD and the potential use of genetic tests in identifying individuals at risk are also discussed. (Clin Mol Hepatol 2017;23:1-12).